1969
DOI: 10.1139/v69-735
|View full text |Cite
|
Sign up to set email alerts
|

Steroids and steroidases. IX. Activation parameters and the mechanism of base- and enzyme-catalyzed isomerizations of androst-5-ene-3,17-dione. The nature of the active center of the Δ5 → Δ4-3-ketosteroid isomerase of Pseudomonas testosteroni

Abstract: Determination of the activation parameters for the acid-, base-, and enzynle-catalyzed isomerizations of androst-5-ene-3.17-dione has revealed that the facility of the enzyn~ic process is mainly due to an extremely low entlialpy of activation of 5.0 kcal mole-'. Further circirn>stantial evidence regarding the nature of the reacting groups at the active center has also been obtained, and a mechanism of cnzyme action is proposed employing tyrosine and histidine as the principal aniino acids responsible for catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

1970
1970
1997
1997

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 6 publications
3
17
0
Order By: Relevance
“…Finally, the activation parameters for both the spontaneous (⌬H ‡ ϭ 15.1 kcal͞mol, ⌬S ‡ ϭ Ϫ14.0 cal͞mol⅐K) and antibody-catalyzed (⌬H ‡ ϭ 12.5 kcal͞mol, ⌬S ‡ ϭ Ϫ5.4 cal͞mol⅐K; for k cat ) reactions were calculated from linear Arrhenius plots. The data for the spontaneous isomerization are in accord with expected values (24).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Finally, the activation parameters for both the spontaneous (⌬H ‡ ϭ 15.1 kcal͞mol, ⌬S ‡ ϭ Ϫ14.0 cal͞mol⅐K) and antibody-catalyzed (⌬H ‡ ϭ 12.5 kcal͞mol, ⌬S ‡ ϭ Ϫ5.4 cal͞mol⅐K; for k cat ) reactions were calculated from linear Arrhenius plots. The data for the spontaneous isomerization are in accord with expected values (24).…”
Section: Resultssupporting
confidence: 87%
“…Whereas the antibody restricts the entropy from being as unfavorable compared with the spontaneous reaction, the enzyme facilitates the isomerization due to an extremely low enthalpy of activation (17). Apparently, covalent catalysis provides a significant entropic advantage in the antibody reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, except for cho!est-5-en-3-one, the isomerization rates for the series la-e are significant even in 30% aqueous methanol. These results indicate that, other than in the region of the ring A binding locus (Talalay, 1965;Malhotra and Ringold, 1965;Sih and Whitlock, 1967;Jones and Wigfield, 1969;Jones and Ship, 1972), the active site of the enzyme is largely nonpolar in character and that formation of the ES complex with hydrophobic substrates protects, at least partially, the active-site region of the isomerase against the inactivating effects of the higher methanol content solutions. The 5-3-8 with the smaller C-17d alkyl groups are the most effective in this regard (Table III).…”
Section: Discussionmentioning
confidence: 93%
“…National Research Council of Canada Scholarship Holder, 1968-1971. and Wigfield, 1968and Wigfield, , 1969; Weintraub et al, 1972), Our previous studies had indicated that A5-3-keto steroids with nonpolar C-17 substituents, such as androst-5-en-3-one (la) and cholest-5-en-3-one (le), were not substrates of the enzyme due to their micellar aggregation in aqueous solvents (Jones and Wigfield, 1968). However, the data suggested that if disaggregation to the fully solvated species could be effected, such molecules would be efficiently isomerized by the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Most likely this results from carboxymethylation by 16 -BAP and 21-BAP of the imidazole ring of a histidine residue at the active site of 3a,20/3-HSD (Ganguly & Warren, 1971;. Histidine has been implicated as an amino acid which participates in hydrogen transfer at the active sites of A5-3-ketosteroid isomerase (Malhotra & Ringold, 1965;Talalay, 1965;Jones & Wigfield, 1969;Benson et al, 1971), lactate dehydrogenase (Ringold, 1966), and glutamate dehydrogenase (Baker, 1967). In the present work the failure to obtain reactivation of 3a,20/3-HSD at pH 9.0 following affinity alkylation with 16a-BAP or 21-BAP (bound to the active site by base-labile ester linkages) suggests that alkylation of the histidine residue impairs its ability to participate in hydrogen transfer at the active site.…”
Section: Discussionmentioning
confidence: 99%